Primary mixed adeno-neuroendocrine carcinoma (MANEC) of the urinary bladder: a rare entity - Eckstein, Markus; Rasper, Bernd; Busche, Joerg; Stachetzki, Ulf; Wistuba, D. E.; Agaimy, Abbas; Hartmann, Arndt; Bertz, Simone (Aktuelle Urologie, 2017)
A 67-year-old male patient underwent transurethral resection for a bladder tumour at the lower posterior wall found incidentally on imaging for an unrelated disease. The initial histomorphological examination suggested an adenocarcinoma with partial neuroendocrine differentiation. Imaging of the thorax and the abdomen, showed no evidence of another primary tumour. Due to the unusual diagnosis, the case was sent to our department of pathology for expert consultation, which confirmed the diagnosis of a primary mixed adeno-neuroendocrine carcinoma of the bladder (MANEC). Mixed adeno-neuroendocrine carcinomas are rare tumours that mostly occur in the colorectum. To our knowledge, this case is the fifth case report of a MANEC primarily arising in the urinary bladder.
EVALuna2:6854